The feasibility of e-encyclopedia on plants structure and function as teaching material for junior high school students in Pontianak - Siti Komaria; Kurnia Ningsih; Titin Titin (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to determine the feasibility and responses of students to the E-Encyclopedia on the structure and function of plants material for the 8th grade of junior high school students. This is a Research and Development (R&D) which consists of 7 stages namely potential and problems, data collection, product design, product design validation, design revision, product testing, and product revision. The instrument used was the validation sheet of the E-Encyclopedia of Plant Structure and Function and a student response questionnaire filled out by 15 respondents. The average result of the validation analysis of Aiken's V E-Encyclopedia of Plant Structure and Function obtained 0,90 is in the valid category, while the reliability value of 0,775 is in the sufficient reliability category. The results of the questionnaire response analysis obtained an average of 77,6%, namely in the strong category. From the results obtained, it can be concluded that the e-encyclopedia is appropriate to be used as teaching material on the Structure and Function of Plants for 8th grades of junior high school.